The Influence Of Overconfidence And Risk Tolerance On Investment Decisions In Capital Markets In Generation Z In Tasikmalaya City - Oktaviani, Indiarti; Yusnita, Rita Tri; Oktaviani, Nita Fauziah (Jurnal Pusat Manajemen, 2025)
The study was carried out in Tasikmalaya City to explore how overconfidence and risk tolerance influence the investment choices of Generation Z individuals in the capital market. The research employed a quantitative approach and survey method. The target population consisted of Generation Z members residing in Tasikmalaya City who are active in the capital market. The sampling technique involved non-probability sampling with a probability approach, resulting in a sample size of 100 individuals between 18 and 27 years old. Both primary and secondary data were collected for this study. The data analysis involved validity and reliability tests, classical hypothesis tests, statistical analysis tests, and hypothesis testing using SPSS version 25. The findings from the F test indicated that both overconfidence and risk tolerance significantly influence investment decisions. However, the t-test results revealed that while risk tolerance has a significant impact on investment decisions, overconfidence doesn’t have a significant effect when considered individually.